Sequestrectomy acute pancreatitis of urgency in necrotic hemorrhagic - Cazabán, Luis A; Baldizán, Jorge W; Carriquiry, Luis A (Cirugía del Uruguay, 1976)
Report of the first published case of acute necrotizing- hemorrhagic pancreatitis treated by removing of pancreatic sequestra, in our country. The authors make a plea for this operation and note the indications and surgical technique, pointing out the need to act systematically llpon the biliary tract. Gastrostomy, feeding jejunostomy and continuous peritoneal lavage, are useful complementary therapeutic measures. The postoperative course of these patients must be followed in an intensive care unit.